2004
DOI: 10.2337/diabetes.53.11.2741
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Hyperinsulinemia in Dogs Augments Access of Macromolecules to Insulin-Sensitive Tissues

Abstract: The present results show that physiological hyperinsulinemia will enhance the delivery of a substance of similar molecular size to insulin to previously less intensively perfused regions of insulin-sensitive tissues. Our data suggest that the delivery of insulin itself to insulin-sensitive tissues could be a mechanism of insulin action on cellular glucose uptake independent of and possibly synergistic with either enhanced blood flow distribution or GLUT4 transporter recruitment to enhance glucose utilization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 35 publications
1
26
1
Order By: Relevance
“…suggested that insulin itself can increase blood flow; neither we nor others have been able to support this result. Interestingly, Ellmerer et al observed insulin's ability to augment the volume of distribution in the interstitial space of sensitive tissues whether by increasing the number of dilated capillaries in the area or by another unidentified mechanism (41). However, the time courses of these changes remain to be determined.…”
Section: Fig 4 Average Time Course Of Net (Injected Leg Corrected Fmentioning
confidence: 99%
See 2 more Smart Citations
“…suggested that insulin itself can increase blood flow; neither we nor others have been able to support this result. Interestingly, Ellmerer et al observed insulin's ability to augment the volume of distribution in the interstitial space of sensitive tissues whether by increasing the number of dilated capillaries in the area or by another unidentified mechanism (41). However, the time courses of these changes remain to be determined.…”
Section: Fig 4 Average Time Course Of Net (Injected Leg Corrected Fmentioning
confidence: 99%
“…We believe our local in vivo method, where comparatively little insulin is administered, more accurately assesses whether the transport of insulin across the vascular wall is altered with insulin resistance. Studies have shown a decrease in insulin-mediated capillary recruitment with various insulin-resistant models (49,50) and a decrease in the distribution volume (41). Thus, a decreased distribution of insulin to sensitive tissues may contribute to insulin resistance with or without affecting the ability of insulin to cross the endothelium.…”
Section: Fig 4 Average Time Course Of Net (Injected Leg Corrected Fmentioning
confidence: 99%
See 1 more Smart Citation
“…4,19 Recently, the effects of systemic insulin infusion on transport and distribution kinetics of the extracellular marker [14C]inulin were studied in an animal model that allowed access to hindlimb lymph, a surrogate for interstitial fluid. 21 Insulin, at physiological concentrations, augments the access of the labeled inulin to insulin-sensitive tissues. In addition, they demonstrated that access of macromolecules to insulin-sensitive tissues is impaired during diet-induced insulin resistance.…”
Section: Microvascular Dysfunction As a Cause Of Insulin Resistancementioning
confidence: 99%
“…Adequate transport of insulin across the capillary wall and its own availability in interstitial fluid of insulin-sensitive tissues have been identified as crucial factors for insulin action (15,16). In a recent study applying a model in dogs, Ellmerer et al (9) suggested that insulin could possibly regulate its own distribution to insulin-sensitive tissues. The same investigators also demonstrated that the observed effect of insulin to recruit additional peripheral distribution volume is reduced after diet-induced insulin resistance.…”
mentioning
confidence: 99%